2015
DOI: 10.1016/j.renene.2015.03.058
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic mooring ropes for marine renewable energy applications

Abstract: Synthetic mooring ropes have a proven track record of use in harsh operating conditions over the past two decades. As one of the main users of ropes for permanent mooring systems, the oil and gas industry has opted for these components because they possess performance characteristics and economies of scale which are in many respects superior to steel components. Given this accrued experience, it is unsurprising that several marine renewable energy (MRE) device developers have utilised synthetic ropes, motivate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(62 citation statements)
references
References 45 publications
1
60
0
1
Order By: Relevance
“…Under some conditions polyester ropes, which are favoured for offshore platform station-keeping, are too stiff for wind turbine moorings, and polyamide may be a suitable alternative. While early studies on fatigue of braided nylon ropes showed very short lifetimes some recent results have indicated that it is possible to significantly enhance lifetime by modifying rope construction and improving fibre coatings [1]. The fatigue results presented here for ropes from a different supplier, confirm this result.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Under some conditions polyester ropes, which are favoured for offshore platform station-keeping, are too stiff for wind turbine moorings, and polyamide may be a suitable alternative. While early studies on fatigue of braided nylon ropes showed very short lifetimes some recent results have indicated that it is possible to significantly enhance lifetime by modifying rope construction and improving fibre coatings [1]. The fatigue results presented here for ropes from a different supplier, confirm this result.…”
supporting
confidence: 79%
“…Since these applications aim at harnessing marine energies, the systems are located on exposed area where dynamic loading are significant. In addition, the inherent moderate to small water depth induce a global stiff behaviour of the mooring system in using standard components as per done for deepwater floating oil platforms [1] (steel chains or polyester rope).…”
Section: Introductionmentioning
confidence: 99%
“…Steel mooring components such as chains and stranded wire ropes are used exclusively. Synthetic fiber ropes can potentially be applied to develop cost-effective designs for the mooring systems of marine renewable energy devices [10]. The material of the mooring line for our ocean-current turbine should be synthetic rope.…”
Section: Mooring Systemmentioning
confidence: 99%
“…The use of synthetic fibre ropes for mooring systems has seen a sudden rise in marine applications over the last two decades [5] albeit mainly for deep water mooring [6]. Experience and feedback from the use of polyester ropes for MRE device moorings is still limited in terms of publications produced.…”
Section: Introductionmentioning
confidence: 99%